Targeting airway smooth muscle in airways diseases: an old concept with new twists. (December 2011) - Koziol-White, Cynthia J; Damera, Gautam; Panettieri, Reynold A
Airway smooth muscle (ASM) manifests a hyper-responsive phenotype in airway disorders such as asthma. ASM also modulates immune responses by secreting mediators and expressing cell-surface molecules that promote recruitment of inflammatory cells to the lungs. The aim of the current article is to highlight therapeutics that may modulate ASM responses in airway disorders and exacerbations.